New sorbicillinoid derivatives with GLP-1R and eEF2K affinities from a sponge-derived fungus Penicillium chrysogenum 581F1. Issue 20 (17th October 2020) - Cao, Min-Jia; Zhu, Tao; Liu, Jing-Tang; Ouyang, Liang; Yang, Fan; Lin, Hou-Wen
Abstract: Two new sorbicillinoids, 13-hydroxy-dihydrotrichodermolide (1 ) and 10, 11, 27, 28-tetrahydrotrisorbicillinone C (2 ), were isolated from the sponge-derived fungus Penicillium chrysogenum 581F1. Their structures were determined on the basis of spectroscopic analysis. Compounds 1 and 2 displayed high affinities to target proteins GLP-1R (diabetes) and eEF2K (cancer) with Kd values of 0.0285 μM, 0.0162 μM for GLP-1R and 0.118 μM, 0.0746 μM for eEF2K, respectively. Graphical Abstract: